Dampak Tindak Pidana Pencurian terhadap Ketertiban Hukum dan Masyarakat - Rio Ferdika; Tamaulina Br. Sembiring; Tubagus Aditya Wardhana; Davina Sarah Azzevi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Criminal offenses of theft are one of the most frequent forms of crime in society and have wide-ranging impacts, not only on the individual victim but also on legal order and social stability. This study aims to analyze the impact of theft offenses on legal order and social life, while also examining the role of criminal law in addressing such crimes. The research method used is qualitative with a descriptive approach through literature study, observation, and interviews with law enforcement officers and the public. The results of the study show that the prevalence of theft offenses can decrease public safety, weaken public trust in law enforcement agencies, and disturb social order and harmony. Furthermore, theft also leads to a decline in legal compliance and an increase in the potential for vigilante justice. Therefore, consistent, effective, and just law enforcement is required, along with increasing public legal awareness as efforts to maintain legal order and create a safe and orderly social life.